Mr Barbecue by Elena Kats-Chernin: The Raw and the Cooked (Journal of Music Research Online, 2022)
This article examines the music theatre work, Mr Barbecue (2002), composed by Elena Kats-Chernin with a libretto by Janis Balodis. It looks at the work within the context of her two previous music theatre works Iphis (1997) and Matricide: The Musical (1998), which I argue express a feminine aesthetic. I refer particularly to Eva Rieger’s theories of the ‘restricted aesthetic’. With the commissioning of Mr. Barbecue, Kats-Chernin was required to set a libretto which expressed the new wave of masculinist thinking that emerged in the 1990s as a backlash against feminism. I hypothesise that Kats-Chernin engaged in this commission for the career opportunities it provided rather than for her interest in the subject matter. The resulting work demonstrates superior compositional expertise, but to a lesser extent, an aesthetic engagement by the composer.I examine her background and training as a composer and how Kats-Chernin is particularly suited to the writing of music with comic twist. I also argue that in setting the songs she resorts to a mode of expression very familiar to her, i.e. cabaret. I also examine the musical setting of the text and her particularly post-modern approach of incorporating an eclectic array of ideas drawn from a wide variety of musical sources.